Skin repair and anti-aging composition and preparation method thereof
By combining silicone oil-nano titanium dioxide complex with vitamin C derivatives, a self-migrating protective film is formed, which solves the problem of declining efficacy of vitamin C with aging and achieves multiple effects of anti-oxidation, moisturizing and skin barrier repair.
Patent Information
- Application Number
- CN202510926907.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-09-19
- Estimated Expiration
- 2045-07-07
AI Technical Summary
Vitamin C derivatives are easily decomposed under light or high temperature conditions, resulting in a significant decrease in their anti-aging effects.
A silicone oil-nano titanium dioxide complex is combined with a vitamin C derivative. Nano titanium dioxide treated with a silane coupling agent forms a complex with cyclopentasiloxane, which is used to self-migrate on the skin surface to form a physical protective film, blocking external factors such as light and oxygen. It is combined with polyether modified silicone and moisturizer to improve stability.
It effectively reduces the photooxidative decomposition rate of vitamin C derivatives, ensures their antioxidant and collagen synthesis-promoting activities, achieves multiple functions such as antioxidant, moisturizing and repairing the skin barrier, and improves product stability and usage experience.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cosmetics and relates to a skin repair and anti-aging composition and a preparation method thereof. Background Art
[0002] In the modern beauty and skincare sector, as people's demands for skin health and appearance continue to rise, the research and development of skin repair and anti-aging products continues to heat up. Currently, various skin repair and anti-aging compositions containing multiple active ingredients are gaining widespread market application due to their multiple benefits, including moisturizing, whitening, and barrier repair. Among them, vitamin C derivatives, due to their excellent anti-aging and repair properties, such as antioxidant properties, collagen synthesis promotion, and reduction of free radical damage, have become key ingredients in many high-end skincare products.
[0003] However, existing vitamin C derivatives have significant drawbacks. They are chemically unstable and easily decompose under light or high temperature, resulting in a significant reduction in the active ingredient content and, in turn, a significant decrease in the product's anti-aging efficacy. Summary of the Invention
[0004] The purpose of the present invention is to provide a skin repair and anti-aging composition and a preparation method thereof, which can achieve multiple functions of anti-oxidation, skin barrier repair and anti-aging by improving the stability of vitamin C derivatives.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a skin repair and anti-aging composition comprising the following components in percentage by mass:
[0007] 0.5-2% vitamin C derivatives;
[0008] 1-2% silicone oil-nano titanium dioxide complex;
[0009] 0.5-1% polyether modified silicone;
[0010] 0.1-0.5% moisturizer;
[0011] 0.2-0.5% thickener;
[0012] 0.5-1.0% preservative;
[0013] The balance is water;
[0014] The silicone oil-nano titanium dioxide composite is composed of cyclopentasiloxane, a silane coupling agent and nano titanium dioxide.
[0015] Preferably, the silicone oil-nano titanium dioxide composite is prepared as follows:
[0016] A1. Mix nano-titanium dioxide and cyclopentasiloxane to form a uniform slurry;
[0017] A2. Adding a silane coupling agent to the slurry, stirring, and drying to obtain the silicone oil-nano titanium dioxide composite.
[0018] Preferably, the mass ratio of the nano-titanium dioxide to cyclopentasiloxane is 1:(1-3).
[0019] Preferably, the added amount of the silane coupling agent is 0.1-0.2% of the mass of the nano-titanium dioxide, and the silane coupling agent is γ-aminopropyltrimethoxysilane or octyltriethoxysilane.
[0020] Preferably, the particle size of the nano-titanium dioxide is 30-100 nm.
[0021] Preferably, the vitamin C derivative is a combination of one or both of tetrahexyldecyl ascorbate and ascorbic acid ethyl ether.
[0022] Preferably, the polyether-modified silicone is PEG-10 polydimethylsiloxane or PEG-20 polydimethylsiloxane.
[0023] Preferably, the moisturizing agent is one or more of sodium hyaluronate, glycerol or pyrrolidone carboxylic acid.
[0024] Preferably, the thickener is carbomer 940 or xanthan gum.
[0025] In a second aspect, the present invention provides a method for preparing the skin repair and anti-aging composition as described above, comprising the following steps:
[0026] S1, mixing a silicone oil-nano titanium dioxide composite, a polyether-modified siloxane, and a vitamin C derivative to obtain a mixed solution a;
[0027] S2, mixing a moisturizer, a thickener, a preservative and water to obtain a mixed solution b;
[0028] S3. Mixing the mixed solution a and the mixed solution b, and emulsifying them to obtain a skin repair and anti-aging composition.
[0029] Beneficial effects of the present invention:
[0030] (1) In the silicone oil-nano titanium dioxide complex, the volatility of cyclopentasiloxane can drive the self-migration of nano titanium dioxide to the skin surface, forming a physical protective film, effectively blocking external factors such as light and oxygen, reducing the photooxidative decomposition rate of vitamin C derivatives, ensuring their anti-oxidation, promoting collagen synthesis and other anti-aging activities, and solving the problem of easy inactivation of vitamin C derivatives in existing technologies.
[0031] (2) Vitamin C derivatives synergistically act as antioxidants, nano-titanium dioxide assists in light protection, moisturizers such as sodium hyaluronate and glycerin deeply lock in moisture and repair the skin barrier, and polyether-modified silicone optimizes skin feel and system stability. Multiple ingredients work together to achieve multiple effects of antioxidant, moisturizing, repairing the skin barrier and delaying aging, meeting the complex needs of skin anti-aging and repair.
[0032] (3) Polyether-modified silicone gives the system good emulsification and smooth skin feel. Cyclopentasiloxane evaporates without leaving any sticky residue. Nano-titanium dioxide self-migrates to form a thin and breathable film, which not only ensures efficacy but also takes into account the user experience, thereby improving the market acceptance of the product. DETAILED DESCRIPTION
[0033] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0034] Example 1
[0035] A skin repair and anti-aging composition comprising the following components in percentage by mass:
[0036] Vitamin C derivative (tetrahexyldecyl ascorbate) 1.0%;
[0037] Silicone oil-nano titanium dioxide complex 1.5%;
[0038] Polyether modified silicone (PEG-10 polydimethylsiloxane) 0.7%;
[0039] Moisturizer (sodium hyaluronate) 0.3%;
[0040] Thickener (Carbomer 940) 0.3%;
[0041] Preservative (phenoxyethanol) 0.7%;
[0042] The balance is water.
[0043] The preparation of silicone oil-nano titanium dioxide composite is as follows:
[0044] A1. Take 10g of nano-titanium dioxide (particle size 50nm) and 20g of cyclopentasiloxane (mass ratio of nano-titanium dioxide to cyclopentasiloxane is 1:2) and add them to a high-speed disperser. Stir at 800 rpm at 25°C for 15 minutes to form a uniform slurry.
[0045] A2. Add 0.015 g of silane coupling agent (γ-aminopropyltrimethoxysilane, accounting for 0.15% of the mass of nano-titanium dioxide) to the slurry, raise the temperature to 40°C, stir at 600 rpm for 30 minutes, and then dry in a vacuum drying oven at 50°C for 2 hours to obtain a silicone oil-nano-titanium dioxide composite.
[0046] A preparation step of a skin repair and anti-aging composition:
[0047] S1. Take 1.5 g of silicone oil-nano titanium dioxide composite, 0.7 g of polyether-modified siloxane, and 1 g of tetrahexyldecyl ascorbate in a beaker and stir at 500 r / min for 10 min at 30 ° C to obtain a mixed solution a;
[0048] S2. Add 0.3 g of sodium hyaluronate, 0.3 g of carbomer 940, 0.7 g of phenoxyethanol, and water (to a total mass of 100 g) to another beaker and stir at 400 rpm at 50°C until completely dissolved to obtain a mixture b.
[0049] S3. Slowly pour the mixed solution a into the mixed solution b, raise the temperature to 60°C, turn on the emulsifier, emulsify at 1200 r / min for 20 minutes, and then naturally cool to room temperature to obtain a skin repair anti-aging composition.
[0050] Example 2
[0051] A skin repair and anti-aging composition comprising the following components in percentage by mass:
[0052] Vitamin C derivative (ascorbic acid ethyl ether) 0.5%;
[0053] Silicone oil-nano titanium dioxide complex 1.0%;
[0054] Polyether modified silicone (PEG-20 polydimethylsiloxane) 0.5%;
[0055] Humectant (glycerin) 0.1%;
[0056] Thickener (xanthan gum) 0.2%;
[0057] Preservative (phenoxyethanol) 0.5%;
[0058] The balance is water.
[0059] The preparation of silicone oil-nano titanium dioxide composite is as follows:
[0060] A1. Take 10g of nano-titanium dioxide (particle size 30nm) and 10g of cyclopentasiloxane (mass ratio of nano-titanium dioxide to cyclopentasiloxane is 1:1) and add them to a high-speed disperser. Stir at 600 rpm at 40°C for 30 minutes to form a uniform slurry.
[0061] A2. Add 0.01 g of silane coupling agent (octyltriethoxysilane, accounting for 0.1% of the mass of nano-titanium dioxide) to the slurry, then raise the temperature to 40°C, stir at 600 r / min for 30 minutes, and then dry in a vacuum drying oven at 50°C for 2 hours to obtain a silicone oil-nano-titanium dioxide composite.
[0062] A preparation step of a skin repair and anti-aging composition:
[0063] S1. Take 1.0 g of silicone oil-nano-titanium dioxide composite, 0.5 g of polyether-modified siloxane and 0.5 g of ascorbic acid ethyl ether in a beaker and stir at 30 ° C at 500 r / min for 10 min to obtain a mixed solution a;
[0064] S2. Add 0.1 g glycerin, 0.2 g xanthan gum, 0.5 g phenoxyethanol, and water (to a total mass of 100 g) to another beaker and stir at 400 rpm at 50°C until completely dissolved to obtain a mixture b.
[0065] S3. Slowly pour the mixed solution a into the mixed solution b, raise the temperature to 60°C, turn on the emulsifier, emulsify at 1200 r / min for 20 minutes, and then naturally cool to room temperature to obtain a skin repair anti-aging composition.
[0066] Example 3
[0067] A skin repair and anti-aging composition comprising the following components in percentage by mass:
[0068] Vitamin C derivative (tetrahexyldecyl ascorbate) 2.0%;
[0069] Silicone oil-nano titanium dioxide complex 2.0%;
[0070] Polyether modified silicone (PEG-10 polydimethylsiloxane) 1.0%;
[0071] Humectant (pyrrolidone carboxylic acid) 0.5%;
[0072] Thickener (Carbomer 940) 0.5%;
[0073] Preservative (phenoxyethanol) 1.0%;
[0074] The balance is water.
[0075] The preparation of silicone oil-nano titanium dioxide composite is as follows:
[0076] A1. Take 10g of nano-titanium dioxide (particle size 100nm) and 30g of cyclopentasiloxane (mass ratio of nano-titanium dioxide to cyclopentasiloxane is 1:3) and add them to a high-speed disperser. Stir at 800 rpm for 15 minutes at 25°C to form a uniform slurry.
[0077] A2. Add 0.02 g of silane coupling agent (γ-aminopropyltrimethoxysilane, accounting for 0.2% of the mass of nano-titanium dioxide) to the slurry, raise the temperature to 40°C, stir at 600 rpm for 30 minutes, and then dry in a vacuum drying oven at 50°C for 2 hours to obtain a silicone oil-nano-titanium dioxide composite.
[0078] A preparation step of a skin repair and anti-aging composition:
[0079] S1. 2.0 g of silicone oil-nano-titanium dioxide composite, 1.0 g of polyether-modified siloxane, and 2 g of tetrahexyldecyl ascorbate were placed in a beaker and stirred at 500 r / min for 10 min at 30 ° C to obtain a mixed solution a;
[0080] S2. Add 0.5 g of pyrrolidone carboxylic acid, 0.5 g of carbomer 940, 1.0 g of phenoxyethanol, and water (to a total mass of 100 g) to another beaker and stir at 400 rpm at 50°C until completely dissolved to obtain a mixture b.
[0081] S3. Slowly pour the mixed solution a into the mixed solution b, raise the temperature to 60°C, turn on the emulsifier, emulsify at 1200 r / min for 20 minutes, and then naturally cool to room temperature to obtain a skin repair anti-aging composition.
[0082] Example 4
[0083] A skin repair and anti-aging composition comprising the following components in percentage by mass:
[0084] Vitamin C derivative (tetrahexyldecyl ascorbate and ascorbic acid ethyl ether, the mass ratio of tetrahexyldecyl ascorbate and ascorbic acid ethyl ether is 1:1) 1.5%;
[0085] Silicone oil-nano titanium dioxide complex 1.2%;
[0086] Polyether modified silicone (PEG-20 polydimethylsiloxane) 0.8%;
[0087] Moisturizer (sodium hyaluronate and glycerin, the mass ratio of sodium hyaluronate and glycerin is 1:1) 0.4%;
[0088] Thickener (xanthan gum) 0.4%;
[0089] Preservative (phenoxyethanol) 0.8%;
[0090] The balance is water.
[0091] The preparation of silicone oil-nano titanium dioxide composite is as follows:
[0092] A1. Combine 10g of nano-titanium dioxide (particle size 50nm) and 20g of cyclopentasiloxane (mass ratio of nano-titanium dioxide to cyclopentasiloxane:1:2) in a high-speed disperser and stir at 800 rpm for 15 minutes at 25°C to form a uniform slurry.
[0093] A2. Add 0.015 g of silane coupling agent (γ-aminopropyltrimethoxysilane, accounting for 0.15% of the mass of nano-titanium dioxide) to the slurry, raise the temperature to 40°C, stir at 600 rpm for 30 minutes, and then dry in a vacuum drying oven at 50°C for 2 hours to obtain a silicone oil-nano-titanium dioxide composite.
[0094] A preparation step of a skin repair and anti-aging composition:
[0095] S1. Take 1.2 g of silicone oil-nano-titanium dioxide composite, 0.8 g of polyether-modified siloxane, and 1.5 g of vitamin C derivative in a beaker and stir at 500 rpm for 10 min at 30 ° C to obtain a mixed solution a;
[0096] S2. Add 0.2 g sodium hyaluronate, 0.2 g glycerin, 0.4 g xanthan gum, 0.8 g phenoxyethanol, and water (to a total mass of 100 g) to another beaker and stir at 400 rpm at 50°C until completely dissolved to obtain a mixture b.
[0097] S3. Slowly pour the mixed solution a into the mixed solution b, raise the temperature to 60°C, turn on the emulsifier, emulsify at 1200 r / min for 20 minutes, and then naturally cool to room temperature to obtain a skin repair anti-aging composition.
[0098] Example 5
[0099] A skin repair and anti-aging composition comprising the following components in percentage by mass:
[0100] Vitamin C derivative (tetrahexyldecyl ascorbate and ascorbic acid ethyl ether, the mass ratio of tetrahexyldecyl ascorbate and ascorbic acid ethyl ether is 1:1) 1.2%;
[0101] Silicone oil-nano titanium dioxide composite 1.8%;
[0102] Polyether modified silicone (PEG-20 polydimethylsiloxane) 0.9%;
[0103] Humectant (pyrrolidone carboxylic acid and glycerin, the mass ratio of pyrrolidone carboxylic acid to glycerin is 1:1) 0.4%;
[0104] Thickener (xanthan gum) 0.3%;
[0105] Preservative (phenoxyethanol) 0.6%;
[0106] Water balance.
[0107] Preparation steps of silicone oil-nano titanium dioxide composite:
[0108] A1: Take 10g of nano-titanium dioxide (particle size 70nm) and 25g of cyclopentasiloxane (mass ratio 1:2.5), add them to a high-speed disperser, and stir at 800r / min at 25°C for 15min to form a uniform slurry;
[0109] A2: Add 0.018 g of silane coupling agent (octyltriethoxysilane, accounting for 0.18% of the mass of nano-titanium dioxide) to the slurry, raise the temperature to 40°C, stir at 600 r / min for 30 minutes, and then dry in a vacuum drying oven at 50°C for 2 hours to obtain a silicone oil-nano-titanium dioxide composite.
[0110] Preparation steps of skin repair and anti-aging composition:
[0111] S1. Place 1.8 g of silicone oil-nano-titanium dioxide composite, 0.9 g of polyether-modified siloxane, and 1.2 g of vitamin C derivative in a beaker and stir at 500 rpm for 10 min at 30 ° C to obtain a mixed solution a;
[0112] S2. Add 0.2 g of pyrrolidone carboxylic acid, 0.2 g of glycerin, 0.3 g of xanthan gum, 0.6 g of phenoxyethanol, and water (to a total mass of 100 g) to another beaker and stir at 400 rpm at 50°C until completely dissolved to obtain a mixture b.
[0113] S3. Slowly pour the mixed solution a into the mixed solution b, raise the temperature to 60°C, start the emulsifier and emulsify at 1200 r / min for 20 minutes, and naturally cool to room temperature to obtain a skin repair and anti-aging composition.
[0114] Comparative Example 1
[0115] The difference from Example 1 is that the silicone oil-nano titanium dioxide complex is not added to the components of the skin repair and anti-aging composition.
[0116] Comparative Example 2
[0117] The difference from Example 1 is that no silane coupling agent is added during the preparation of the silicone oil-nano titanium dioxide composite.
[0118] Comparative Example 3
[0119] The difference from Example 1 is that the particle size of the nano titanium dioxide is 200 nm.
[0120] Comparative Example 4
[0121] The difference from Example 1 is that the mass ratio of nano-titanium dioxide to cyclopentasiloxane is adjusted to 1:0.5.
[0122] Comparative Example 5
[0123] The difference from Example 1 is that no polyether-modified silicone is added to the components of the skin repair and anti-aging composition.
[0124] Test Case
[0125] 1. Accelerated photostability test
[0126] Method: 50 ml of the composition of Examples 1-5 and Comparative Examples 1-5 were placed in a transparent glass bottle and exposed to UVA light at 45°C and 10 mW / cm² for 168 hours (simulating 6 months of natural sunlight). Samples were taken every 24 hours, and the residual vitamin C derivative was determined by HPLC. The specific steps were as follows: 1 mL of sample was added to 4 mL of methanol, vortexed for 10 minutes, and centrifuged at 10,000 rpm for 10 minutes. The supernatant was filtered through a 0.22 μm filter membrane and separated on a C18 column (250 mm × 4.6 mm, 5 μm) using a mobile phase of methanol and 0.1% phosphoric acid (20:80, v / v) at a flow rate of 1.0 mL / min, a column temperature of 30°C, a detection wavelength of 245 nm, and an injection volume of 10 μL.
[0127] Evaluation Criteria: Calculate the residual rate of the vitamin C derivative at each time point based on the initial concentration using the formula: Residual Rate (%) = (C_t / C_0) × 100% (C_t is the concentration at time t, C_0 is the initial concentration). A residual rate ≥ 90% after 168 hours is considered excellent, 80%-89% is acceptable, and <80% is unacceptable.
[0128] 2. Antioxidant capacity test (DPPH free radical scavenging rate)
[0129] Methods: 0.1 mL of the composition of Examples 1-5 and Comparative Examples 1-5 was mixed with 2.9 mL of DPPH solution (0.1 mmol / L). The mixture was shaken at 25°C in the dark for 30 minutes. The absorbance was measured at 517 nm. A blank control group (0.1 mL of ethanol and 2.9 mL of DPPH solution), a negative control group (0.1 mL of sample and 2.9 mL of ethanol), and a positive control group (0.1% pure vitamin C derivative solution) were also set up.
[0130] Evaluation Criteria: Calculate the DPPH radical scavenging rate using the formula: Scavenging Rate (%) = [1 - (A Sample - A Blank) / A Negative] × 100%, where A Sample represents the absorbance of the sample group, A Blank represents the absorbance of the blank group, and A Negative represents the absorbance of the negative control group. A higher scavenging rate indicates stronger antioxidant capacity.
[0131] 3. Dynamic test of surface protection performance
[0132] Method: Sample Application and Preparation: 0.5 mL of each composition from Example 1 and Comparative Examples 1-5 was evenly applied to a clean glass slide (25 mm x 75 mm) to form a film approximately 0.1 mm thick, avoiding air bubbles and accumulation. The following tests were performed on the sample surface at 0 min, 30 min, 1 h, and 2 h after application.
[0133] Ultraviolet transmittance determination: Use a UV-visible spectrophotometer equipped with an integrating sphere (wavelength range 200-400nm). Perform a blank calibration before testing. Use an unsmeared glass slide as a reference. Adjust the instrument so that the baseline transmittance is 100% over the entire band. Then place the sample-smeared glass slide at the test port and record the transmittance in the UVA band (320-400nm) and UVB band (280-320nm).
[0134] The specific data of Test Case 1 and Test Case 2 are shown in Table 1.
[0135] The specific data of Test Example 3 is shown in Table 2.
[0136] Table 1
[0137] sample 168h Vitamin C residual rate (%) DPPH clearance rate (%) Example 1 96.3 82.5 Example 2 94.8 80.2 Example 3 97.1 83.7 Example 4 95.6 81.9 Example 5 96.8 83.2 Comparative Example 1 68.4 61.3 Comparative Example 2 85.7 72.1 Comparative Example 3 80.2 74.5 Comparative Example 4 82.6 73.9 Comparative Example 5 92.4 78.6
[0138] Table 2
[0139]
[0140] As shown in Table 1, the vitamin C derivatives of Examples 1-5 all exhibited residual rates exceeding 94% after 168 hours of illumination, with DPPH scavenging rates ranging from 80.2% to 83.7%. In contrast, the residual rate of Comparative Example 1 (no complex) was only 68.4%, with a scavenging rate of 61.3%. This indicates that the silicone oil-nano-titanium dioxide complex significantly enhances the stability and antioxidant activity of vitamin C derivatives. The residual rates of Comparative Example 2 (no silane coupling agent), Comparative Example 3 (nano-titanium dioxide particle size 200 nm), Comparative Example 4 (silicone oil to nano-titanium dioxide mass ratio of 1:0.5), Comparative Example 5 (no polyether-modified silicone), and Comparative Example 5 (no polyether-modified silicone) were all lower than those of the Examples. This demonstrates that the synergistic effects of silane coupling agent coating, appropriate particle size, silicone oil ratio, and polyether-modified silicone are key to ensuring the functionality of the complex.
[0141] As shown in Table 2, within 2 hours after application, the UVA transmittance of Example 1 increased from 14.2% to 18.3%, and the UVB transmittance increased from 9.7% to 12.6%. The transmittance increases were slow and remained low. However, the UVA transmittance of Comparative Example 1 (no composite) reached 46.1% for UVA and 33.8% for UVB, significantly higher than those of the Example, confirming that the silicone oil-nano-titanium dioxide composite can form an effective light-protective film. The transmittances of Comparative Examples 2 (no coupling agent), 3 (excessive particle size), 4 (insufficient silicone oil ratio), and 5 (no polyether-modified silicone) were all higher than those of the Example, demonstrating that silane coupling agent treatment enhances the dispersibility of nano-titanium dioxide, that the appropriate particle size and silicone oil ratio promotes its self-migration and film formation, and that the polyether-modified silicone optimizes film uniformity and adhesion. Combined with the volatility characteristics of silicone oil, it can be seen that during the volatilization process of cyclopentasiloxane, it drives nano-titanium dioxide to migrate to the skin surface and self-assemble into a film. This dynamic film-forming process causes the UVA / UVB transmittance to slowly increase over time, but always maintains a low transmittance state, achieving long-term light protection.
[0142] In summary, this composition constructs a dynamic photoprotection system through the self-migration film-forming mechanism of the silicone oil-nano-titanium dioxide complex. The volatility of cyclopentasiloxane acts as a driving force, prompting the directional migration of nano-titanium dioxide to the skin surface, forming a continuous and thin protective film that significantly reduces the photooxidative effects of ultraviolet light on vitamin C derivatives and UV radiation damage. At the same time, the synergistic effect of the polyether-modified siloxane and the silane coupling agent ensures the dispersion stability and film-forming uniformity of the complex in the system, creating a synergistic effect between the antioxidant activity of the vitamin C derivative and the photoprotective properties of the nano-titanium dioxide, ultimately achieving a dual enhancement in the stabilization of the active ingredient and the anti-aging efficacy of the skin.
[0143] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can, without departing from the scope of the technical solution of the present invention, make some changes or modifications to equivalent embodiments using the technical contents disclosed above. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A skin repair and anti-aging composition, characterized in that: The following components are included in mass percentage: 0.5-2% vitamin C derivatives; 1-2% silicone oil-nano titanium dioxide complex; 0.5-1% polyether modified silicone; 0.1-0.5% moisturizer; 0.2-0.5% thickener; 0.5-1.0% preservative; The balance is water; The silicone oil-nano titanium dioxide composite is composed of cyclopentasiloxane, a silane coupling agent and nano titanium dioxide; The preparation of the silicone oil-nano titanium dioxide composite is as follows: A1. Mix nano-titanium dioxide and cyclopentasiloxane to form a uniform slurry; A2. adding a silane coupling agent to the slurry, stirring, and drying to obtain the silicone oil-nano titanium dioxide composite; The mass ratio of the nano-titanium dioxide to cyclopentasiloxane is 1:(1-3); The amount of the silane coupling agent added is 0.1-0.2% of the mass of the nano-titanium dioxide, and the silane coupling agent is γ-aminopropyltrimethoxysilane or octyltriethoxysilane; The particle size of the nano titanium dioxide is 30-100 nm.
2. A skin repair and anti-aging composition according to claim 1, characterized in that: The vitamin C derivative is a compound of one or both of tetrahexyldecyl ascorbate and ascorbic acid ethyl ether.
3. A skin repair and anti-aging composition according to claim 1, characterized in that: The polyether-modified silicone is PEG-10 polydimethylsiloxane or PEG-20 polydimethylsiloxane.
4. A skin repair and anti-aging composition according to claim 1, characterized in that: The moisturizing agent is one or more of sodium hyaluronate, glycerin or pyrrolidone carboxylic acid.
5. A skin repair and anti-aging composition according to claim 1, characterized in that: The thickener is carbomer 940 or xanthan gum.
6. A method for preparing the skin repair and anti-aging composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing a silicone oil-nano titanium dioxide composite, a polyether-modified siloxane, and a vitamin C derivative to obtain a mixed solution a; S2, mixing a moisturizer, a thickener, a preservative and water to obtain a mixed solution b; S3. Mixing the mixed solution a and the mixed solution b, and emulsifying them to obtain a skin repair and anti-aging composition.
Citation Information
Patent Citations
Preparation method of environment-friendly solvent-free self-cleaning anti-glare glass coating
CN105273608A
Cosmetic powder, oily color paste and preparation method thereof
CN108272648A